“STABILITAS LERENG PROYEK PEMBANGUNAN JALAN TOL SOLO – NGAWI – KERTOSONO PAKET 1 STA. 91+850” - Djoko Susilo Adhi; Abdul Rochim; Nur Faridha; Safiera Putri (UNISSULA Semarang, 2019)
ABSTRACTFor the regional goverment, the presence of the Solo – Kertosono toll road will be an alternative route free of obstacles abd reduce the travel time for vehicle users going to Solo from the direction of Kertosono and vice versa. So from that comfort and safety for users need to be considered in order to minimize the occurrence of traffic accidents.In this Final Project the methods used are he calculation of the soil carrying capacity of the Terzaqi method, manual security number with the Bishop method, security figures with the use of PLAXIS v8.2 and GEOSTUDIO 2018 applications. Where Mohr – Coulomb collapse adn plastic properties as a soil model. The purpose of this study is to evaluate and compare the calculation of soil analysis with exixting secondary data.Obtained soil carrying capacity of 578,374 kN/m2 and allowable carrying capacity of 444,903 kN/m2, safety factor (SF) of the three analyze resulted in a figure above 1,5 or a result above the safety rate in the long term. Keywords: Bishop, Geostudio, Plaxis, Soil Carrying Capacity. ABSTRAKBagi pemerintah daerah kehadiran jalan tol Solo – Kertosono akan menjadi jalur alternatif bebas hambatan dan mengurangi waktu tempuh bagi pengguna kendaraan yang akan menuju Solo dari arah Kertosono maupun sebaliknya. Maka dari itu kenyamanan dan keamanan bagi pengguna perlu diperhatikan demi meminimalisisr terjadinya kecelakaan lalu lintas.Metode yang digunakan adalah perhitungan daya dukung tanah metode Terzaqi, angka keamanan manual dengan metode Bishop, angka keamanan dengan penggunaan aplikasi PLAXIS v8.2 serta GEOSTUDIO 2018. Pada keruntuhan Mohr-Coulomb serta sifat plastis sebagai model tanah. Tujuan dari penelitian ini adalah untuk mengevaluasi dan membandingkan dari perhitungan analisis tanah dengan data sekunder yang sudah ada.Didapatkan hasil daya dukung tanah 578,374 kN/m2 dan daya dukung tanah yang diijinkan 444,903 kN/m2, angka keamanan (SF) dari ketiga analisis tersebut menghasilkan angka diatas 1,5 atau hasil diatas angka keamanan dalam jangka panjang.Kata Kunci: Bishop, Daya Dukung Tanah, Geostudio, Plaxis.